2020
DOI: 10.1158/2326-6066.cir-20-0149
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Integrated Image-Based Immune and Molecular Profiling in Early-Stage Endometrial Cancer

Abstract: Optimum risk stratification in early-stage endometrial cancer (EC) combines clinicopathological factors and the molecular EC classification defined by The Cancer Genome Atlas (TCGA). It is unclear whether analysis of intratumoral immune infiltrate improves this. We developed a machine-learning image-based algorithm to quantify density of CD8 + and CD103 + immune cells in tumor epithelium and stroma in 695 stage I endometrioid ECs from the PORTEC-1&-2 trials. The relationship between immune cell density and cli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 43 publications
7
61
0
Order By: Relevance
“…This study applies a digital quantification method, 20 employing deep neural networks for tissue segmentation, to determine the infiltration patterns of single CD8, single CD103 and CD8CD103 TRM in HGSOC, and to investigate the impact of the spatial distribution of immune cells in the tumor microenvironment on clinical outcomes. We demonstrate that high CD8CD103 TRM infiltration is associated with improved survival in HGSOC patients; however, this survival benefit is restricted to completely debulked PDS patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study applies a digital quantification method, 20 employing deep neural networks for tissue segmentation, to determine the infiltration patterns of single CD8, single CD103 and CD8CD103 TRM in HGSOC, and to investigate the impact of the spatial distribution of immune cells in the tumor microenvironment on clinical outcomes. We demonstrate that high CD8CD103 TRM infiltration is associated with improved survival in HGSOC patients; however, this survival benefit is restricted to completely debulked PDS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Infiltration of three immune cell subsets was assessed; CD8 + CD103 − (single CD8), CD8 − CD103 + (single CD103) and CD8 + CD103 + TRM cells (CD8CD103 TRM) in different locations; the epithelium and stromal compartments (Figure 1). 20 Hierarchical clustering revealed that patients were clustered together based on infiltration of the various cell subsets, independent of location (Figure 2(a)). In addition, there was apparent heterogeneity in the degree of single CD8, single CD103 and CD8CD103 TRM infiltration with a subgroup of patient samples infiltrated by single CD8 cells or single CD103 cells, but not CD8CD103 TRM cells.…”
Section: Patterns Of Infiltration Of the Cd8cd103 Immune Cell Subsetsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently demonstrated that assessment of CD8 + tumor in ltrating Tlymphocytes (TILs) improves prognostication beyond clinicopathological risk factors and molecular class. 1 In another study, we found that T-cell responses led to B-cell driven immune responses via the secretion of CLCX13, a key driver of B-cell recruitment. 2 Expression of CLCX13 was associated with the formation of B-cell aggregates in and around ECs in the presence of high endothelial venules (HEV), germinal B-cells centers and dendritic cells surrounded by a rim of T-cells.…”
Section: Introductionmentioning
confidence: 93%
“…2 Immunohistochemistry for CD8 + and CD20 + was carried out using a modi cation of a previously reported protocol. 1,2 ). Unstained epithelium and stromal broblasts served as internal negative controls.…”
Section: Patient Materialsmentioning
confidence: 99%